Foreword: In Memory of Lord Cooke - Butler, Petra (Victoria University of Wellington Law Review, 2008)
This foreword introduces the articles published in this issue which celebrates the life of one of New Zealand's finest jurists, Lord Cooke. The range of articles in this issue exemplifies the wide range of interests Lord Cooke had and his ability to frame the most complicated issues in basic principles.